2020
DOI: 10.1097/pec.0000000000002011
|View full text |Cite
|
Sign up to set email alerts
|

The Use of PECARN and CATCH Rules in Children With Minor Head Trauma Presenting to Emergency Department 24 Hours After Injury

Abstract: Objective: Major studies (PECARN [Pediatric Emergency Care AppliedResearch Network], CATCH [Canadian Assessment of Childhood Head Injury]) that regulate the use of computed tomography (CT) algorithms in children with minor head trauma (MHT) have been conducted among children presenting in 24 hours after injury. In this study, we aimed to compare use and results of PECARN and CATCH rules in children presenting in and after 24 hours following injury.Methods: Records of children who were admitted to emergency dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 18 publications
(36 reference statements)
2
12
0
Order By: Relevance
“…It has also been suggested that the scores that are currently available effectively predict the occurrence of significant injuries 18 . In contrast, data on paediatric patients have shown some conflicting results 12,13,15,19–21 . In our study, 4.1% of the cases presented to the emergency department 24 h after sustaining a minor head trauma, which was similar to other studies 13 …”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…It has also been suggested that the scores that are currently available effectively predict the occurrence of significant injuries 18 . In contrast, data on paediatric patients have shown some conflicting results 12,13,15,19–21 . In our study, 4.1% of the cases presented to the emergency department 24 h after sustaining a minor head trauma, which was similar to other studies 13 …”
Section: Discussionsupporting
confidence: 84%
“…Risk group and imaging findings in children who presented early or late and underwent a neuroimaging study results. 12,13,15,[19][20][21] In our study, 4.1% of the cases presented to the emergency department 24 h after sustaining a minor head trauma, which was similar to other studies. 13 There was a slightly higher median age in the late access group, which reflected the tendency to take young infants to emergency departments earlier than older children, regardless of their symptoms.…”
Section: Ta B L Esupporting
confidence: 91%
See 2 more Smart Citations
“…Majority of past studies related to cranial CT decisionmaking aimed to identify ciTBI requiring acute intervention, particularly neurosurgery. 3,4,[10][11][12] CT scan is performed only when ciTBI is suspected to reduce the risk of exposure to radiation; however, ciTBI has an extremely low incidence in the range of 0.67% to 1.13%. 3,11 TBIs such as numerous skull fractures and ciTBI are observed in less than 10% of CT scans in children with minor head trauma.…”
Section: Discussionmentioning
confidence: 99%